Evaluation of comingling pigs before weaning to reduce weaning stress - Thulin, A.J.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to evaluate the management practice of comingling litters one week before weaning to help reduce weaning stress. Pigs which were comingled before weaning gained slightly faster the first two weeks after weaning than pigs mixed at weaning, but overall pig performance to 7 to 8 weeks of age was similar for rate of gain and feed efficiency.
Keywords: Swine; Comingling pigs; Stress; Rate of gain; Feed eficiency